108 Service Evaluation Regarding the Implementation of the National Early Warning Score 2 (NEWS2) in Palliative Care. (14th March 2023) - Webster, Grace; Farrington, Clare; Vedder, Rachel; Stroud, David
Abstract : Introduction: NEWS2 has been shown to improve outcomes in areas including mortality and serious adverse events. 1, 2 Little is known about its use in palliative care. A CQC review recommended NEWS2 be implemented at Barnsley Hospice to aid identification of deteriorating patients. This raised concerns whether this would impact on individualised holistic hospice care. Our neighbouring hospice St Gemma's kindly shared their guidelines and escalation form regarding incorporating NEWS2. Following implementation all patients on admission would have an escalation form documenting discussions regarding frequency of routine observations, baseline NEWS2, escalation and resuscitation status. The purpose of this service evaluation was to assess whether the escalation tool and NEWS2 could be appropriately embedded within the hospice and enhance patient care. Methods: Data was collected weekly from 9.10.22 to 25.10.22 recording whether patients had an escalation form completed on admission. It also recorded whether they had a NEWS2 and whether this had been escalated appropriately, based upon their clinical status and agreed treatment plan. Results: A total of 51 data sets were collected. This included 26 patients, some of whom had multiple data sets due to admission length. All 51 data sets had an escalation form completed. 76% had a NEWS2 chart in place. The remaining 24% were all supported by a last days of life care plan. Out of the 111 observations recorded only one was not escalated appropriately. In this case twice daily observations had been part of the treatment plan but on one occasion they had only been done once daily. There was no clinical impact of this. Conclusions: The NEWS2 was appropriately implemented at Barnsley Hospice to support the recognition of patients who are clinically deteriorating and may benefit from escalation. In addition, rather than detract from delivering holistic care it has supported escalation discussions and advance care planning. References: Credland N, Dyson J, Johnson MJ. Do early warning track and trigger tools improve patient outcomes? A systematic synthesis without meta-analysis. Journal of Advanced Nursing, 2021;77 (2):622–634. Royal College of Physicians 2017. RCP London National Early Warning Score (NEWS) 2, accessed 27/10/22. <https://www.rcplondon.ac.uk/projects/outputs/national-early-warning-score-news-2>